Electric power distribution, automation, protection, and control - Momoh, James A., ....- (Boca Raton : CRC, 2008)
Presenting updated concepts and applications for engineers and students, "Electric Power Distribution, Automation, Protection, and Control" lays a foundation in distribution system automation functions, base grids for protection systems, reliability assessment, and new trends in intelligent systems and communications to enhance performance. This book covers distribution modeling topics that include components representative of distribution systems, such as transformers, bus junctions, feeds, loads, and fuses. It also addresses issues related to distributed generation options, protection, maintenance, and control strategies, reliability and control methods, and micro-grids.
Keywords: Elektriciteitsvoorziening